Bunraku : - Ando, Tsuruo (Walker/Weatherhill, 1970)
This book takes the reader directly into the Bunraku thater and behind the scenes for a look at its history, its techniques, and its repertoire. the approach is largerly visual one, as the generous selection of illustrations makes clear. puppet types, scenes from famous plays, views of onstage and backstage activity, drawings and paintings from Bunraku's long history all these complement a text that re-creates the actual atmostphere of the theater and provides as many pleasures as the pictures themselves.